Tumour related inhibition of macrophage chemotaxis in patients with colon cancer. Issue 4 (April 1987) - Hermanowicz, A; Gibson, P R; Jewell, D P
Abstract : The chemotactic migration in vitro of peripheral blood, intestinal mucosal, and mesenteric lymph node mononuclear cells has been assessed in patients with colorectal carcinoma. Peripheral blood mononuclear cells of patients exhibited normal chemotaxis. For control patients with non-malignant, non-inflammatory intestinal disease, the chemotaxis of mucosal mononuclear cells was similar to that of autologous peripheral blood mononuclear cells. The chemotactic migration of mucosal mononuclear cells, however, isolated distant from a colon cancer was less than that of autologous peripheral blood mononuclear cells. Chemotactic migration was progressively impaired with increasing closeness to the tumour itself. Chemotaxis of mucosal mononuclear cell was independent of the site of tumour and the Dukes' grading. Mononuclear cells from mesenteric lymph nodes, however, exhibited impaired migration only in patients with Dukes' C tumours. Supernatants of the collagenase digestion of either tumour or adjacent mucosa contained macrophage directed inhibitors of chemotaxis and these inhibitors were not produced by tumour mononuclear cells. The presence of such inhibitors in the digestion supernatants and the demonstration that proximity to the tumour was associated with impaired mononuclear cell motility suggest that the production of macrophage directed chemotactic inhibitors is by colon cancer cells and that this may be occurring in vivo.